Hollow core optical fibers - Belardi, Walter (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The possibility of guiding light in air has fascinated optical scientists and engineers since the dawn of optical fiber technology. In the last few years, hollow core optical fibers have been attracting the attention of an expanding worldwide research community, furthering the design, fabrication and device implementation of specialty optical fibers. Hollow core optical fibers are entering almost any specific application field of optics from medicine to security; from telecommunication to industrial processing; from instrumentation to biology. In parallel to the increased number of applications, major advances are still being made on the optimization of hollow core fiber designs and on the study of its underlying guiding properties, as well as in the use of different materials and fabrication techniques, which, in turn, are providing even more ways of exploitation of this technology and new technical challenges. This Special Issue of Fibers rides the wave of this increasing interest in the field of hollow core optical fibers by providing an overview of the recent progress in this field as well as an updated and indicative sample of current research activities worldwide.